2012
DOI: 10.1194/jlr.m022558
|View full text |Cite
|
Sign up to set email alerts
|

Global changes in phospholipids identified by MALDI MS in rats with focal cerebral ischemia

Abstract: has been given to cellular phospholipid analyses compared with protein or peptide analyses. However, recent progress in mass spectrometric analysis has enabled the identifi cation of small cellular components including phospholipids and quantifi cation of their cellular expression profi les ( 3, 4 ).ESI MS is widely used for phospholipid analysis. Currently, MALDI imaging MS (MALDI IMS) has become the prime choice because it provides additional advantages over ESI, including simple sample preparation and an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…For example, the new mass spectroscopic technique MALDI MS revealed the changes of phospholipids, such as lysophosphatidylcholine, phosphatidylcholine, phosphatidylethanolamine, and sphingomyelin, in rat brains after focal cerebral ischemia (26). Studies have revealed that inducible Hsp70.1 has protective effects against ischemia and oxidative injury (27,28); however, whether its protection correlates with membrane lipids remains to be elucidated.…”
Section: Journal Of Biological Chemistry 27439mentioning
confidence: 99%
“…For example, the new mass spectroscopic technique MALDI MS revealed the changes of phospholipids, such as lysophosphatidylcholine, phosphatidylcholine, phosphatidylethanolamine, and sphingomyelin, in rat brains after focal cerebral ischemia (26). Studies have revealed that inducible Hsp70.1 has protective effects against ischemia and oxidative injury (27,28); however, whether its protection correlates with membrane lipids remains to be elucidated.…”
Section: Journal Of Biological Chemistry 27439mentioning
confidence: 99%
“…As PLs constitute the majority of the biological molecules in cells and whole tissues that are analyzed in MALDI-MS experiments (9)(10)(11), this is a useful method to monitor PL changes in certain biological states. After adipose tissue, brain tissue contains the second highest concentration of PLs (20-25%) (12)(13)(14). MALDI IMS has emerged as the prime choice for PL analysis because it provides advantages over other ionization methods such as ESI MS, including simple sample preparation and the inclusion of spatial information ( 15,16 ).…”
Section: Ims Analysismentioning
confidence: 99%
“…Brains from three mice were analyzed for each experimental group. Following the whole tissue IMS analysis, the data were analyzed using FlexImaging and ClinProTools, as described previously ( 12 ). Figure 2 presents a comparison of the average spectra obtained from the whole brain tissue sections after normalization using ClinProTools 2.2 in positive ( Fig.…”
Section: Tissue Distribution Analysis Of Selected Pls By Imsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 LysoPC(16:0) by itself increases on brain after stroke 20,21 where it mediates phagocyte recruiting 22 that can contribute to ischemic brain injury 23 and also produces neuroinflammatory effects when applied on CNS. 24 All these results could pinpoint a beneficial effect of reduced LysoPC(16:0) levels that argue against our claim that it marks an early SR risk, but although high levels of plaque LysoPC(16:0) are correlated with high plasma and plaque levels of Lp-PLA2, plasma LysoPC(16:0) levels are not.…”
mentioning
confidence: 99%